Cell death in the developing vertebrate limb: A locally regulated mechanism contributing to musculoskeletal tissue morphogenesis and differentiation. Issue 9 (2nd September 2020) - Montero, Juan A.; Lorda‐Diez, Carlos I.; Sanchez‐Fernandez, Cristina; Hurle, Juan M.
Abstract: Our aim is to critically review current knowledge of the function and regulation of cell death in the developing limb. We provide a detailed, but short, overview of the areas of cell death observed in the developing limb, establishing their function in morphogenesis and structural development of limb tissues. We will examine the functions of this process in the formation and growth of the limb primordia, formation of cartilaginous skeleton, formation of synovial joints, and establishment of muscle bellies, tendons, and entheses. We will analyze the plasticity of the cell death program by focusing on the developmental potential of progenitors prior to death. Considering the prolonged plasticity of progenitors to escape from the death process, we will discuss a new biological perspective that explains cell death: this process, rather than secondary to a specific genetic program, is a consequence of the tissue building strategy employed by the embryo based on the formation of scaffolds that disintegrate once their associated neighboring structures differentiate. Key Findings: We examine the functions of cell death in the formation and growth of the limb primordia. We analyze the plasticity of the cell death program by focusing on the developmental potential of progenitors prior to death. Considering the prolonged plasticity of progenitors to escape from the death process and the absence of defined genetic program in their regulation we propose that cell death is a consequence of the tissue building strategy employed by the embryo regulated by epigenetic factors .